Human monkeypox — After 40 years, an unintended consequence of smallpox eradication - Shah, Hussain Haider; Molani, Muhammad Khizer; Shabbir, Naqiha (Frontiers in Public Health, 2023)
Monkeypox is one of the many zoonotic viruses that belong to the Orthopoxvirus genus of the Poxviridae family with a similar clinical appearance to smallpox. The symptoms of monkeypox include fever, headache, muscle aches, and lymphadenopathy. The transmission of monkeypox occurs from infected animals to humans or through direct contact (sexual or skin-to-skin), respiratory droplets, and clothing such as towels. The incidence of monkeypox is rising drastically over the world. This short communication discusses the causes of the rising monkeypox cases and emphasizes strategies to prevent the spread of the virus.